Một số giải pháp tháo gỡ những khso khăn nảy sinh trong quá trình công nghiệp hóa, hiện đại hóa nông nghiệp - nông thôn - Xuân, Mai Thị Thanh (VNU Journal of Science: Legal Studies; Vol 20 No 4, 2004)
In the processing of industialization and modernization the agriculture and rural, there are some new difficults appear such as the increase of extra-labor in rural area, the transaction of land in rural area can affect the food reserves, the gap between areas and professions, the over-stock of goods,... The solutions are: speed up in developing the profession, scheme the land logically, subsidize the difficulty areas, develop the rural market...